The assessment of Bosnian EFL learners’ knowledge by two different measures: test and writing assignment - Tankosić, Ana; Dubravac, Vildana (ExELL, 2025)
(BIH). However, since the number of English classes per week is very limited they should be utilized in the best possible way to produce proficient users of English. Nowadays, when language proficiency is viewed as one’s ability to speak and write in the target language and not about it, the need for the proficiency evaluation in schools arises. The present study attempts to shed a spot of light on this issue, investigating two very common ways of assessing students’ knowledge in schools, namely tests and writing assignments. Hence, through the interviews with English teachers and the analysis of students’ tests and writing assignments, the current paper explores the ways in which these two measures are realized, the tasks they consist of, the type of linguistic knowledge they are used to evaluate, their levels of difficulty, and the type of corrective feedback teachers provide on both of them. The results suggest that teachers on both measure rather students’ explicit than their implicit knowledge, focusing much more on accuracy than fluency development.